Vetus Latina: Die Reste der altlateinischen Bibel. 11/2. Sirach (Ecclesiasticus). Edited by Walter Thiele. Vetus Latina: Die Reste der altlateinischen Bibel. 11/2. Sirach (Ecclesiasticus). Edited by Walter Thiele. Vetus Latina: Die Reste der altlateinischen Bibel. 11/2. Sirach (Ecclesiasticus). Edited by Walter Thiele - Elliott, J. K. (The journal of theological studies, 2007)
Sirach contains fifty-two chapters. The three fascicules noticed here take us from Sir. 16:21 to 24:47, and include a Stellenregister (normally found only at the end of a Vetus Latina volume). The reason for this index is that it is here—at the end of chapter 24—where Dr Thiele has finally laid down his editorial pen. Thiele began work on this volume of Vetus Latina in 1987. At 83 years of age he has now finally retired from a lifetime's scholarly activity on the Latin Bible. We wish him well in his richly deserved retirement but trust Prof. Roger Gryson, the director of the project, is able to find a successor to complete the Vetus Latina Sirach., Fascicules 1–3 were reviewed in JTS 42 (1991), pp. 179–81 and fascicules 4–6 in vol. 48 (1997), pp. 565–7.